Verkörperte Heterotopien: Zur Materialität und [Un-]Ordnung ganz anderer Räume - Maurer, Susanne; Scholle, Jasmin; Wuttig, Bettina; Spahn, Lea (transcript, 2017)
As lived somatic realities and forms of practice, heterotopias form (im)possible places of confrontation/interaction. The contributions to this book question the materiality and (dis)orderings of these 'completely other spaces'. Throughout, corporeality remains the central point of reference in this analysis and helps concentrate the transdisciplinary examination on the (self-) realisations of the moving, somatic subject, as well as collective or institutionalised practices. The diverse theoretical perspectives present in this book open a horizon that comprises living intensities and abilities to act but also the fragile and critical.